2023
DOI: 10.1101/2023.11.06.565717
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome analysis of the mouse fetal and adult rete ovarii and surrounding tissues

Dilara N. Anbarci,
Rebecca O’Rourke,
Yu Xiang
et al.

Abstract: The rete ovarii (RO) is an epithelial structure that arises during fetal development in close proximity to the ovary and persists throughout adulthood in mice. However, the functional significance of the RO remains elusive, and it has been absent from recent discussions of female reproductive anatomy. The RO comprises three distinct regions: the intraovarian rete (IOR) within the ovary, the extraovarian rete (EOR) in the periovarian tissue, and the connecting rete (CR) linking the EOR and IOR. We hypothesize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 31 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…A protein that was prominent on the proteomic candidate list was IGFBP2. We found that Igfbp2 was highly expressed in both the embryonic and adult RO transcriptome (Anbarci et al, 2023). IGFBP2 is an ideal candidate protein to mediate ovarian function.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…A protein that was prominent on the proteomic candidate list was IGFBP2. We found that Igfbp2 was highly expressed in both the embryonic and adult RO transcriptome (Anbarci et al, 2023). IGFBP2 is an ideal candidate protein to mediate ovarian function.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, the ovary and surrounding tissue are more highly innervated than the testis (McKey et al, 2019). A surprising finding in our bulk transcriptome analysis of the RO was the presence of a high proportion of immune cells and cells with vascular markers that co-isolated with E16.5 RO cells (Anbarci et al, 2023).…”
Section: Integration Of the Eor With The Extra-ovarian Environmentmentioning
confidence: 82%
See 3 more Smart Citations